Dendrokronološka analiza debelinskega priraščanja smreke (Picea abies (L.) Karst.) na območju njene naravne in umetne razširjenosti v Sloveniji - Stopar, Samo (Acta silvae et ligni, 2018)
A dendrochronological analysis of the spruce's radial increment at eight different plots was conducted throughout Slovenia. The plots selected were diverse: five of them were natural spruce stands; in others, the spruce was introduced anthropogenically in the past for economic reasons, or its natural share in stands was increased. We took samples of at least 20 trees per plot and examined them in the dendrochronological laboratory using Advanced Tree-Ring Image Capturing System (ATRICS) and specialized dendrochronological software. We compared the growth in natural spruce stands with the secondary (anthropogenic) ones and found no statistical differences in growth patterns between these two groups. However, we found some evidence for climate change effect on radial increment at locations Sorško polje, Ravnik and Mašun, which indicates that air temperature and precipitation now have stronger effect on spruce growth than in the past. Analysis of pointer years suggests that extreme events (exceptionally warm and dry years) are more common and widespread in the last 30 years.
Keywords: anthropogenically changed spruce stands; antropogeno spremenjena rastišča smreke; climate change; debelinski prirastek; dendrochronology; dendrokronologija; klimatske spremembe; naravna smrekova rastišča; natural spruce stands; radial increment; Slovenia; Slovenija